PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN RITEL SUB-SEKTOR DEPARTMENT STORE/FASHION YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) - Ayu Lestari; Andy Lasmana; Maria Magdalena Melani (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the effect of receivable turnover and inventory turnover on profitability in retail companies within the department store/fashion sub-sector listed on Indonesia Stock Exchange during 2020-2025 period. This research employed a quantitative method with descriptive and verification approaches. Secondary data obtained from companies’ financial statement were analyzed using multiple linear regression, supported by the coefficient of determination (R2), F-test, and t-test. The result indicate that receivables turnover and inventory turnover simultaneously have a significant effect on profitability. The coefficient on determination (R2) of 32,2% indicates that variation in profitability can be explained by receivables turn over, while the remaining 67,8% is influenced by other factor outside the research model. These findings suggest that effective receivable management play an important role in improving the profitability of retail companies in the department store/fashion sub-sector whereas inventory management does not necessarily contribute significantly to profitability.